AN ACTIVE NOISE CONTROLLER USING TYPE-2 FUZZY NEURAL NETWORK - Tuấn, Huỳnh Văn; Cường, Trần Quốc; Nghĩa, Dương Hoài; Phương, Nguyễn Hữu (Vietnam Journal of Science and Technology, 2012)
SUMMARYThis paper presents a feedback active noise control system using type-2 fuzzy neural network. The new features of the proposed system are: firstly we introduce a saturation compensator for the actuator and secondly we use a type 2 fuzzy neural network to estimate the nonlinearity of the secondary path transfer function. Online dynamic back-propagation learning algorithm based on the error gradient descent method is proposed. The condition of convergence of the proposed algorithm is derived using a discrete Lyapunov function. Simulation results show that the proposed method is effective.